A Simple Method for Eye Protection During Prone Positioning for Craniofacial Surgery. (March 2022) - Grant, Jaime; Noons, Peter; Carver, Edmund D.; Evans, Martin J.; White, Nicholas; Dover, M. Stephen; Rodrigues, Desiderio
Surgery in the prone position risks vision loss due to a number of factors. Craniofacial surgery poses an even greater risk due to the anatomical and physiological makeup of these patients. Here, we describe a novel method of providing protection from direct pressure on the globe during prone positioning for craniofacial procedures and our protocol for improving safety and reducing the risk of postoperative vision loss.